Broadcasting and telecommunications industries in the convergence age: Toward a sustainable public-centric public interest - Choi, Hwanho (Sustainability (Switzerland), 2018)
The emergence of new digital technologies, such as the Internet and new business models such as over-the-top (OTT) operators that utilize them, has transformed the media and broadcasting industries. As advanced technologies and business models are adopted, convergence between the broadcasting and telecommunication ("telecom") sectors has become a common business practice. Using the South Korean case study of a failed acquisition attempt of CJ HelloVision by SK Telecom, this research identifies the three essential features (economic, sociocultural, and industrial structure issues) related to convergence in the broadcasting and media industries. Further, this study reveals the potential consequences of convergence to the public, industry, and society, and offers critical implications for future policy direction. Finally, this study suggests the need for a change in the policy direction in the age of convergence in the broadcasting and media industries. In addition, it calls for the importance of a public-centric public benefit. Social and consumer welfare, and not profit or industrial growth, should dictate the public interest orientation in the broadcasting and media industries. Therefore, the meaning of public interest in broadcasting and media should not be limited in the industrial context of media; rather, it should consider the access to service by the public, the condition of consumption, and its consequences in the perspective of social and consumer welfare.
Keywords: Broadcasting; Convergence; Public interest; Sustainability; Telecommunications